Relationship Between Adequacy of Breastfeeding and The Incidence of Neonatal Jaundice in The NICU at Darus Syifa’ Islamic Hospital Surabaya - Syaiful, Yuanita; Fatmawati, Lilis; Sumiyati, Sumiyati (Caring: Indonesian Journal of Nursing Science, 2023)
Inappropriate early breastfeeding is associated with reduced caloric intake and increased serum bilirubin. It occurs due to a lack of caloric intake to increase enterohepatic circulation. Early breastfeeding for neonates can reduce the occurrence of jaundice. This study aimed to determine the relationship between adequacy breastfeeding and the incidence of neonatal jaundice at the Darus Shifa Islamic Hospital Surabaya. This study used an analytical research design with a cross-sectional approach and a purposive sampling method. The population of this study was 35 respondents. The sample in this study was 32 respondents, and there were two variables. The dependent variable was the adequacy of breastfeeding using an instrument on an observation sheet. The independent variable was the incidence of jaundice using a checklist instrument. Data analysis used Spearman rho. The results of the statistical analysis test using the Spearman rho statistic test with the help of SPSS obtained a significance value of p = 000 which means there is a relationship between the adequacy of breastfeeding. The incidence of neonatal jaundice is r =0,912, meaning there is a solid correlation between the adequacy of breastfeeding and the incidence of it. Adequacy breastfeeding is one way to prevent neonatal jaundice with the support of professional health workers' information to mothers about breastfeeding and its benefits. Thereby affecting the continuity of mothers in breastfeeding so that babies do not experience neonatal jaundice.